The effects of physical and psychological stress on the behaviour and neurochemistry of rats - Van Vuuren, Petra J. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSCMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2005.